Questionnaire to evaluate the dysfunctionalities of the temperomandibular joints in rheumatoid arthritis - Rhys, Karen Vanesa (2021)
Fil: Rhys, Karen Vanesa. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Fisiología; Argentina.